Fibre Bragg grating sensors for the analysis of pressure distribution at a disc brake/pad interface - Major, B. T.; Tiwari, Divya; Correia, Ricardo N.; James, Stephen W.; Tirovic, Marko; Tatam, Ralph P. (SPIE - International Society for Optics and Photonics, 2017)
The use of optical fibre Bragg gratings (FBGs) to monitor the Interface Pressure Distribution (IPD) on an automotive disc brake pad under a variety of loading conditions is studied. The results demonstrate successful strain transfer from the brake pads to the attached FBG sensors under static loading, with a linear response to increasing pressure, and with the measured IPD showing good agreement with that recorded using pressure sensitive paper. Results are also presented demonstrating that changes in the IPD as a result of torque acting on the brake pads can be monitored by the FBG sensors.